2021
DOI: 10.54386/jam.v21i3.249
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impact of thermal units on growth and development of mustard varieties grown under optimum sown conditions

Abstract: Thermal unit indices have a strong correlation with the phenology, growth and yield of crops and can be effectively used to select suitable crop cultivars for specific environmental conditions especially temperature. In this study, four mustard varieties (viz., 'BARI Sharisha-14', 'BARI Sharisha-15', 'BARI Sharisha-16' and 'Tori-7') were grown in two consecutive growing to assess the impact of thermal unit indices on crop growth and development, and to select the suitable variety for better yield under optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Higher temperatures during the early growth phases of rice at Mohanpur might have contributed to faster vegetative growth from sowing to tillering. Islam et al (2019) reported distinct variations in the duration of phenological stages mainly due to the thermal environment of the crop. The rate of tillering in rice tends to increase under an elevated temperature regime.…”
Section: Effect Of Sowing Environment On Rice Phenophasementioning
confidence: 99%
“…Higher temperatures during the early growth phases of rice at Mohanpur might have contributed to faster vegetative growth from sowing to tillering. Islam et al (2019) reported distinct variations in the duration of phenological stages mainly due to the thermal environment of the crop. The rate of tillering in rice tends to increase under an elevated temperature regime.…”
Section: Effect Of Sowing Environment On Rice Phenophasementioning
confidence: 99%